Hubungan antara Kualitas Pelayanan Karyawan Penyandang Disabilitas dengan Kepuasan Konsumen - Dea Nabila Fitri; Ani Yuningsih (Bandung Conference Series: Public Relations, 2023)
Abstract. The phenomenon of using the services of persons with disabilities at Café More is interesting to study because there tends to be a negative stigma for Café More. This research is important to examine because it can determine whether or not there is an influence of service quality of employees with disabilities on customer satisfaction. This study entitled "The Relationship Between Service Quality for Employees with Disabilities and Consumer Satisfaction". Using the theory presented by Tjiptono and Chandra, namely service quality as a form of effort in realizing the needs, desires of buyers, and the accuracy of delivery of these products in order to balance the expectations of buyers. The benefit of this research is to prove to entrepreneurs that there is a positive relationship between service quality and customer satisfaction. The method used in this study is a quantitative method with a quantitative approach, correlation studies and a positivistic paradigm. The population taken by the researchers were Cafe More consumers during November-December 2022. And the sample was taken to be used as respondents using a random random sampling technique. The data collection technique used in this study was through a questionnaire in the form of a Google form and conducting additional interviews to complete the data needed by the researcher. The results of this study are that there is a positive relationship between the service quality of employees with disabilities and customer satisfaction. So that there is no discrimination against employees with disabilities. Abstrak. Fenomena penggunaan pelayanan penyandang disabilitas pada Café More menjadi menarik untuk diteliti karena cenderung adanya stigma negatif untuk Café More. Penelitian ini penting untuk diteliti karena dapat mengetahui ada atau tidaknya pengaruh kualitas pelyanan karyawan penyandang disabilitas dengan kepuasan konsumen. Penelitian ini berjudul “Hubungan Antara kualitas Pelayan Karyawan Penyandang Disabilitas dengan Kepuasan Konsumen”. Mengunakan teori yang dipaparkan oleh Tjiptono dan Chandra yaitu kualitas pelayanan sebagai bentuk upaya dalam mewujudkan kebutuhan, keinginan pembeli, serta ketepatan penyampaian produk tersebut agar dapat mengimbangi harapan pembeli. Manfaat penelitian ini untuk membuktikan kepada para pengusaha bahwa terdapat hubungan yang positif antara hubungan kualitas pelayanan dengan kepuasan konsumen. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan pendekatan kuantitatif, studi korelasi dan paradigma positivistik. Populasi yang diambil oleh peneliti ialah konsumen Cafe More selama bulan November-Desember 2022. Dan menarik sample untuk dijadikan responden dengan Teknik random sampling acak. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah melalui kuesioner berupa Google form dan melakukan wawancara tambahan untuk melengkapi data yang dibutuhkan peneliti. Hasil dari penelitian ini yaitu terdapat hubungan yang positif antara kualitas pelayanan karyawan penyandang disabilitas dengan kepuasan konsumen. Sehingga tidak ada lagi destriminasi terhadap karyawan penyandang disabilitas.